ECLOSION RHYTHM AND ITS ENTRAINMENT BY PHOTOPERIODISM IN OPISINA ARENOSELLA WALKER (LEPIDOPTERA : XYLORYCTINAE) - BABU, P.B. SANTHOSH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
Pupal eclosion in O. arenosella starts usually from about 2 hours after the beginning of the scotophase and ceases 2 hours after midnight. Peak period of adult emergence is between 10 PM and 12 PM. There is an early preponderence of males emerging from a brood. Pupae subjected to constant light condition show the same rhythm of eclosion. Eclosion is also rhythmic when animals are subjected to constant light throughout their life from larval emergence from eggs to adult emergence, The eclosion rhythm in this animal is not entrained by the daily photoperiodism when the animals are subjected to it from early larval stages.